Formal Entrepreneurial Education as a Catalyst for Economic Growth: A Study of Developing Countries With a Focus on India - Tiwari, Priyanka (Digital Repository of Theses, 2024)
This thesis explores the crucial elements that impact the success of entrepreneurs in India, investigating the influence of professional networks, age, education, and the effectiveness of existing support policies. Using quantitative surveys, the research gathers perspectives from various Indian entrepreneurs, providing a comprehensive view of the challenges and motivations behind entrepreneurial endeavours in a rapidly changing economy. The research results emphasize the significance of robust professional networks for accessing essential resources, guidance, and opportunities. It also underscores the unique contributions of entrepreneurs from different age groups. Younger entrepreneurs are recognized for their flexibility and innovative approaches. In comparison, older entrepreneurs bring valuable experience and established networks to the forefront. These insights can serve as inspiration and encouragement, suggesting that support systems should be tailored to meet entrepreneurs' specific needs and strengths at different stages of life. A considerable part of the study is dedicated to the influence of entrepreneurial education, highlighting the importance of practical, skills-based learning in securing funding and effectively managing ventures. The analysis indicates that educational programs should incorporate practical experiences, financial literacy, and strategic planning to prepare entrepreneurs for real-world challenges better. The assessment of entrepreneurial support policies reveals significant deficiencies. Entrepreneurs express worries about inadequate financial support, bureaucratic hurdles, and a need for more encouragement for innovation. These findings indicate an urgent need for comprehensive reforms to create a more favourable environment for entrepreneurial success. The thesis concludes with strategic recommendations for policymakers, educational institutions, and business incubators. Your involvement in implementing these recommendations is critical. These recommendations include enhancing networking opportunities, adjusting initiatives to cater to the diverse age groups in the entrepreneurial community, revising educational curricula to focus on practical skills, and reforming policies to streamline bureaucratic processes and increase support for financial and innovative activities. Your active engagement in these changes will be pivotal in fostering a more supportive entrepreneurial environment in India. The underlying study offers valuable insights and practical recommendations that could cultivate a more vibrant and supportive entrepreneurial environment in India, contributing to broader economic development. The findings are particularly relevant for those involved in shaping policies, designing educational programs, and supporting business incubation activities aimed at nurturing entrepreneurs' growth.